The Meaning of Register in Yoga from a Sociolinguistic Perspective - Lailiyah, Nur; Waryanti, Endang (Universitas Dian Nuswantoro, 2023)
This study describes the form and meaning of registers in yoga in Kediri and explores the influence on yoga practitioners (yogis). The data sources for this research consisted of informants, including Acarya (instructors) and Yogis, while the data was in the form of lexicons uttered by Yogis and Acarya. Data were collected by observing techniques with advanced techniques; listening, engaging, and talking. The data analysis technique uses the theory of register forms resulting from a combination adapted to the register forms in yoga. This study found that there were 53 registers in yoga exercises consisting of two forms, namely, single and complex. There are 29 singular forms and 24 complex forms. The yoga register also strongly influences Yogis (doers), including spirituality, attitudes, and relationships with others. Also, it overcomes health problems faced daily which focus on meditation activities. Meanwhile, the meaning of register in the choice of speech style is intended by Acharya to inspire enthusiasm and freshness in communicating; besides that, it also marks a communication function that has the uniqueness of being a registered marker that has a specific meaning based on context.